FEM simulation of static test with imprecise set up - Zhou, Genggeng (Nanyang Technological University, 2023)
This Final Year Project (FYP) delved into understanding the effect of misalignment in Finite Element Method (FEM) simulations of static tensile tests. For numerical validation of the experimental outcomes, the ANSYS commercial FEA software was employed. The modeling of the specimen was facilitated using SolidWorks. The chosen material for the test specimen was Aluminium alloy 6061-T6. For the quasi-static simulations, isotropic elasticity and multilinear hardening material models were adopted to delineate both the elastic and plastic regions of the material. For dynamic simulations, the Johnson-Cook strength model was employed, given its aptness for materials experiencing extensive strains at elevated strain rates. Concurrently, the Johnson-Cook failure model was integrated into the simulation to offer a holistic view of the material's fracture behaviour. A combination of both static and dynamic simulations could provide a comprehensive view of the material behaviour. Static analysis can offer a baseline understanding of stress distributions, deformation patterns, and potential initiation sites for cracks. When complemented with dynamic analysis, this approach can capture the difference in fracture surface due to misalignment.